Correlation between diffusion and kinetic behaviour of metal hydride battery: voltammetry and impedance analyses - Ika Dewi Wijayanti; Delia Salsabila Putri; Farhan Dzikriansyah; Indra Sidharta; Sutikno Sutikno (Journal of Electrochemical Science and Engineering)
The performance of metal hydride batteries depends on their electrochemical and kinetic behaviour, which varies with the state of charge (SoC). This study explores these characteristics in nickel-metal hydride batteries with A2B7 and AB5 electrodes, focusing on how SoC influences ion diffusion and charge transfer kinetics of the batteries. Electro¬chemical impedance spectroscopy and cyclic voltammetry (CV) were used to analyse these behaviours, while X-ray diffraction provided structural insights and scanning electron microscopy proposed morphological concepts. Results reveal a positive correlation between SoC and both diffusion and kinetic behaviour. The value of fitting resistances decreases as SoC increases, reaching a minimum at 100 % SoC, where hydrogen diffusion is optimized. CV data supports this phenomenon, showing a more negative peak cathodic current (Ip,c) at higher SoC, indicating improved kinetics likely due to enhanced ion availability. Additionally, voltage window analysis showed maximum hydrogen storage at 100 % SoC for AB5 and 50 % for A2B7. Structurally, larger particle sizes and crystallites at higher SoC correlate with increased hydrogen desorption capacity. A2B7 exhibited superior diffusion kinetics, while AB5 demonstrated better discharge behaviour, highlighting how SoC-dependent diffusion and kinetics impact Ni-MH performance.